Activated carbon electrode material for supercapacitor and preparation process of activated carbon electrode material

By introducing zinc gluconate and carbon nanofibers into the activated carbon electrode material to form a honeycomb porous structure, the problems of difficult entry of electrolyte ions and high resistance are solved, and the capacitance performance and service life of the supercapacitor are improved.

CN120622485AActive Publication Date: 2025-09-12福建韩研环保科技有限公司

Patent Information

Application Number
CN202510920454.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-04
Publication Date
2025-09-12
Estimated Expiration
2045-07-04

AI Technical Summary

Technical Problem

Existing activated carbon electrode materials in supercapacitors have problems such as difficulty for electrolyte ions to enter the micropores, large resistance, and severe attenuation of specific capacitance values ​​at high current density, which affects their service life and capacitance performance.

Method used

Sucrose is used as the carbon source, and zinc gluconate is introduced to assist in forming a honeycomb pore framework. Through carbonization, pulse activation and water vapor pore expansion processes, combined with carbon nanofibers and PTFE binders, a conductive network is constructed to improve ion transmission efficiency and capacitance performance.

Benefits of technology

It improves the ion transmission efficiency of the activated carbon electrode material, reduces the loss of specific capacitance value under high current density, enhances the capacitance performance and conductivity, and extends the service life of the supercapacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to an activated carbon electrode material for a supercapacitor and a preparation process thereof, and belongs to the technical field of activated carbon electrode materials. The preparation process provided by the invention specifically comprises the following steps: mixing cane sugar, ammonium dihydrogen phosphate, deionized water and zinc gluconate, carrying out spray drying at 80 DEG C to obtain precursor powder with a loose structure, carbonizing, then carrying out pulse activation, water vapor reaming, cooling and post-treatment, mixing the obtained composite material with carbon nanofibers, a PTFE binder and absolute ethyl alcohol, and carrying out ball milling, so as to obtain the carbon nanofiber composite material. And coating the obtained slurry with an aluminum foil, drying, rolling, and carrying out hot press molding, thereby obtaining the product. According to the invention, cane sugar is used as a carbon source, zinc gluconate is introduced to assist in forming a honeycomb-shaped pore frame, and a honeycomb-shaped porous structure is formed along with further increase of carbonization temperature and multiple cyclic pulse activation and water vapor chambering processes, so that the ion transmission efficiency is improved, and the loss of a specific capacitance value under high current density is reduced; the capacitance performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of activated carbon electrode materials and relates to an activated carbon electrode material for supercapacitors and a preparation process thereof. Background Art

[0002] Supercapacitors are energy storage devices that lie between traditional capacitors and batteries. Their core function is to efficiently store and release energy in a short period of time. They are suitable for scenarios that require fast charging and discharging and high power output, and are widely used in various fields such as hybrid vehicles and smart electronic products. The electrode material of a supercapacitor is a key factor in determining its performance. Activated carbon has become the most commonly used electric double-layer electrode material in supercapacitors due to its low cost, large specific surface area, well-developed pores, and easy preparation. However, the limitations of activated carbon electrode materials in use are also quite obvious. For example, the pores of activated carbon with a large specific surface area are mostly micropores, which make it difficult for electrolyte ions to enter. In addition, the resistance of activated carbon is relatively large, and the specific capacitance value decays relatively severely at high current density, which in turn affects the discharge function of large currents and the service life of supercapacitors. These issues need to be further resolved. Summary of the Invention

[0003] The purpose of the present invention is to provide an activated carbon electrode material for supercapacitors and a preparation process thereof. The present invention uses sucrose as a carbon source and introduces zinc gluconate to assist in forming a honeycomb pore framework. As the carbonization temperature is further increased, and multiple cycles of pulse activation and water vapor pore expansion processes are performed, a honeycomb porous structure is formed, thereby improving ion transmission efficiency, reducing the loss of specific capacitance value under high current density, and improving the capacitance performance of the material.

[0004] The purpose of the present invention can be achieved through the following technical solutions: A process for preparing an activated carbon electrode material for a supercapacitor, the process comprising the following steps: Step 1: After sucrose, ammonium dihydrogen phosphate, and deionized water are uniformly stirred, zinc gluconate is added, mixed, and spray-dried at 80° C. to obtain a precursor powder with a loose structure; Step 2: Carbonizing the precursor powder with a loose structure and then performing pulse activation, steam pore expansion, cooling, and post-processing to obtain a composite material; Step 3: After the composite material, carbon nanofibers, and PTFE binder are evenly mixed, anhydrous ethanol is added, ball milled, and allowed to stand for degassing to obtain a slurry; Step 4: Coat the slurry on aluminum foil, dry it, roll it, and hot-press it to obtain the product.

[0005] Furthermore, the mass ratio of sucrose, ammonium dihydrogen phosphate, deionized water, and zinc gluconate in step 1 is 1-1.2:0.2-0.3:10-12:0.15-0.25.

[0006] Furthermore, the mixing in step 1 refers to stirring at 80-160 rpm for 30-40 min in a 60° C. water bath.

[0007] Furthermore, the carbonization in step 2 refers to heating the temperature to 240-280°C at a heating rate of 4-6°C / min under a nitrogen atmosphere, keeping the temperature for 25-35 minutes, and then heating the temperature to 640-660°C at a heating rate of 8-12°C / min, and keeping the temperature for 0.8-1.2 hours.

[0008] Furthermore, the pulse activation in step 2 refers to first heating the temperature to 760-800°C at a heating rate of 18-22°C / min, keeping it warm for 8-12 minutes, then cooling it to 680-720°C, keeping it warm for 25-35 minutes, and repeating this heating-keeping-cooling-keeping operation twice.

[0009] Furthermore, the water vapor pore expansion in step 2 refers to heating the sample to 760-780° C. at 1-2° C., then introducing water vapor at a flow rate of 55-65 mL / min for 13-15 minutes.

[0010] Furthermore, the post-treatment in step 2 refers to washing with 0.1 mol / L HCl at room temperature for 20 min, rinsing with deionized water until neutral, and vacuum drying at 80°C.

[0011] Furthermore, the mass ratio of the composite material, carbon nanofiber, PTFE binder and anhydrous ethanol in step three is 2.5-2.9:0.4-0.8:2.2-2.6:3.6-4.2.

[0012] Furthermore, the ball milling in step 3 refers to ball milling at a rotation speed of 120-160 rpm for 2.1-2.3 hours.

[0013] Furthermore, the slurry coating amount in step 4 is 1.4-1.8 mg; the specification of the aluminum foil is 1 cm×1 cm; the drying refers to drying in an oven at 60°C for 10 minutes; the rolling temperature is 80°C; and the hot pressing molding refers to hot pressing at 120°C and 10PMa for 5 minutes.

[0014] Beneficial effects of the present invention: (1) The present invention uses sucrose as a carbon source and introduces zinc gluconate at the same time. By spray drying at 80°C, a loose structured precursor powder is formed while preventing the zinc gluconate from decomposing prematurely, which is beneficial to the subsequent activation. When the zinc gluconate reaches the first carbonization temperature, zinc oxide particles and gas are initially generated to assist in forming a honeycomb pore framework. With the further increase of the carbonization temperature, as well as multiple cycles of pulse activation and water vapor pore expansion processes, a honeycomb porous structure is formed, thereby improving the ion transmission efficiency, reducing the loss of specific capacitance value under high current density, and improving the capacitance performance of the material. On this basis, the present invention further introduces carbon nanofibers to construct a conductive network to make up for the insufficient conductivity of activated carbon and reduce the limitation of internal resistance on power output.

[0015] (2) The zinc gluconate in the present invention generates zinc oxide particles and gas at high temperature, wherein the zinc oxide exists as a pore expansion template, which is removed in the subsequent pickling step and further pore expansion; in addition, zinc gluconate may have zinc residues under high temperature treatment, resulting in a zinc-doped carbon skeleton, thereby enhancing the electronic conductivity and synergistically improving the capacitance performance of the material. DETAILED DESCRIPTION

[0016] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0017] Zinc gluconate in all the examples and comparative examples of the present invention was purchased from Hubei Shiteng Chemical Technology Co., Ltd. with a CAS number of 4468-02-4; carbon nanofibers were purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd. with a CAS number of 308068-56-6.

[0018] Example 1 A process for preparing an activated carbon electrode material for a supercapacitor, the process comprising the following steps: Step 1: After sucrose, ammonium dihydrogen phosphate, and deionized water are uniformly stirred, zinc gluconate is added, mixed, and spray-dried at 80° C. to obtain a precursor powder with a loose structure; Step 2: Carbonizing the precursor powder with a loose structure and then performing pulse activation, steam pore expansion, cooling, and post-processing to obtain a composite material; Step 3: After the composite material, carbon nanofibers, and PTFE binder are evenly mixed, anhydrous ethanol is added, ball milled, and allowed to stand for degassing to obtain a slurry; Step 4: Coat the slurry on aluminum foil, dry it, roll it, and hot-press it to obtain the product.

[0019] The mass ratio of sucrose, ammonium dihydrogen phosphate, deionized water, and zinc gluconate in step 1 is 1:0.2:10:0.15.

[0020] The mixing in step 1 refers to stirring at 80 rpm for 30 min in a 60°C water bath.

[0021] The carbonization in step 2 refers to heating the sample to 240°C at a heating rate of 4°C / min under a nitrogen atmosphere, keeping the temperature for 25 minutes, then heating the sample to 640°C at a heating rate of 8°C / min, and keeping the temperature for 0.8 hours.

[0022] The pulse activation in step 2 refers to first heating the temperature to 760°C at a heating rate of 18°C / min, keeping the temperature for 8 minutes, then cooling the temperature to 680°C, keeping the temperature for 25 minutes, and repeating the heating-keeping-cooling-keeping operation twice.

[0023] The water vapor pore expansion in step 2 refers to heating the sample at 1°C to 760°C, introducing water vapor at a flow rate of 55 mL / min, and treating the sample for 13 minutes.

[0024] The post-treatment in step 2 is washing with 0.1 mol / L HCl at room temperature for 20 min, rinsing with deionized water until neutral, and drying in vacuo at 80°C.

[0025] The mass ratio of the composite material, carbon nanofiber, PTFE binder and anhydrous ethanol in step 3 is 2.5:0.4:2.2:3.6.

[0026] The ball milling in step 3 refers to ball milling at a speed of 120 rpm for 2.1 hours.

[0027] In step 4, the amount of slurry applied is 1.4 mg; the specification of the aluminum foil is 1 cm×1 cm; the drying refers to drying in an oven at 60°C for 10 minutes; the rolling temperature is 80°C; and the hot pressing refers to hot pressing at 120°C and 10PMa for 5 minutes.

[0028] Example 2 A process for preparing an activated carbon electrode material for a supercapacitor, the process comprising the following steps: Step 1: After sucrose, ammonium dihydrogen phosphate, and deionized water are uniformly stirred, zinc gluconate is added, mixed, and spray-dried at 80° C. to obtain a precursor powder with a loose structure; Step 2: Carbonizing the precursor powder with a loose structure and then performing pulse activation, steam pore expansion, cooling, and post-processing to obtain a composite material; Step 3: After the composite material, carbon nanofibers, and PTFE binder are evenly mixed, anhydrous ethanol is added, ball milled, and allowed to stand for degassing to obtain a slurry; Step 4: Coat the slurry on aluminum foil, dry it, roll it, and hot-press it to obtain the product.

[0029] The mass ratio of sucrose, ammonium dihydrogen phosphate, deionized water, and zinc gluconate in step 1 is 1.06:0.23:10.5:0.18.

[0030] The mixing in step 1 refers to stirring at 100 rpm in a 60° C. water bath for 31 min.

[0031] The carbonization in step 2 refers to heating the sample to 250°C at a heating rate of 4.5°C / min under a nitrogen atmosphere, keeping the temperature for 28 minutes, and then heating the sample to 645°C at a heating rate of 9°C / min, keeping the temperature for 0.9 hours.

[0032] The pulse activation in step 2 refers to first heating the temperature to 770°C at a heating rate of 19°C / min, keeping the temperature for 9 minutes, then cooling the temperature to 690°C, keeping the temperature for 27 minutes, and repeating the heating-keeping-cooling-keeping operation twice.

[0033] The water vapor pore expansion in step 2 refers to heating the sample by 1°C to 765°C, and then introducing water vapor at a flow rate of 58 mL / min for 13 minutes.

[0034] The post-treatment in step 2 is washing with 0.1 mol / L HCl at room temperature for 20 min, rinsing with deionized water until neutral, and drying in vacuo at 80°C.

[0035] The mass ratio of the composite material, carbon nanofiber, PTFE binder and anhydrous ethanol in step 3 is 2.6:0.5:2.3:3.8.

[0036] The ball milling in step 3 refers to ball milling at a speed of 130 rpm for 2.1 hours.

[0037] In step 4, the amount of slurry coated is 1.5 mg; the specification of the aluminum foil is 1 cm×1 cm; the drying refers to drying in an oven at 60°C for 10 minutes; the rolling temperature is 80°C; and the hot pressing molding refers to hot pressing at 120°C and 10PMa for 5 minutes.

[0038] Example 3 A process for preparing an activated carbon electrode material for a supercapacitor, the process comprising the following steps: Step 1: After sucrose, ammonium dihydrogen phosphate, and deionized water are uniformly stirred, zinc gluconate is added, mixed, and spray-dried at 80° C. to obtain a precursor powder with a loose structure; Step 2: Carbonizing the precursor powder with a loose structure and then performing pulse activation, steam pore expansion, cooling, and post-processing to obtain a composite material; Step 3: After the composite material, carbon nanofibers, and PTFE binder are evenly mixed, anhydrous ethanol is added, ball milled, and allowed to stand for degassing to obtain a slurry; Step 4: Coat the slurry on aluminum foil, dry it, roll it, and hot-press it to obtain the product.

[0039] The mass ratio of sucrose, ammonium dihydrogen phosphate, deionized water, and zinc gluconate in step 1 is 1.1:0.5:11:0.2.

[0040] The mixing in step 1 refers to stirring at 100 rpm in a 60° C. water bath for 35 min.

[0041] The carbonization in step 2 refers to heating the temperature to 260°C at a heating rate of 5°C / min under a nitrogen atmosphere, keeping the temperature for 30 minutes, then heating the temperature to 650°C at a heating rate of 10°C / min, and keeping the temperature for 1 hour.

[0042] The pulse activation in step 2 refers to first heating the temperature to 780°C at a heating rate of 20°C / min, keeping the temperature for 10 minutes, then cooling the temperature to 700°C, keeping the temperature for 30 minutes, and repeating the heating-keeping-cooling-keeping operation twice.

[0043] The water vapor pore expansion in step 2 refers to heating the sample at 1.5°C to 770°C, then introducing water vapor at a flow rate of 60 mL / min for 14 minutes.

[0044] The post-treatment in step 2 is washing with 0.1 mol / L HCl at room temperature for 20 min, rinsing with deionized water until neutral, and drying in vacuo at 80°C.

[0045] The mass ratio of the composite material, carbon nanofiber, PTFE binder and anhydrous ethanol in step 3 is 2.7:0.6:2.4:3.9.

[0046] The ball milling in step 3 refers to ball milling at a speed of 140 rpm for 2.2 h.

[0047] In step 4, the amount of slurry coated is 1.6 mg; the specification of the aluminum foil is 1 cm×1 cm; the drying refers to drying in an oven at 60°C for 10 minutes; the rolling temperature is 80°C; and the hot pressing molding refers to hot pressing at 120°C and 10PMa for 5 minutes.

[0048] Example 4 A process for preparing an activated carbon electrode material for a supercapacitor, the process comprising the following steps: Step 1: After sucrose, ammonium dihydrogen phosphate, and deionized water are uniformly stirred, zinc gluconate is added, mixed, and spray-dried at 80° C. to obtain a precursor powder with a loose structure; Step 2: Carbonizing the precursor powder with a loose structure and then performing pulse activation, steam pore expansion, cooling, and post-processing to obtain a composite material; Step 3: After the composite material, carbon nanofibers, and PTFE binder are evenly mixed, anhydrous ethanol is added, ball milled, and allowed to stand for degassing to obtain a slurry; Step 4: Coat the slurry on aluminum foil, dry it, roll it, and hot-press it to obtain the product.

[0049] The mass ratio of sucrose, ammonium dihydrogen phosphate, deionized water, and zinc gluconate in step 1 is 1.13:0.27:11.4:0.22.

[0050] The mixing in step 1 refers to stirring at 140 rpm in a 60° C. water bath for 38 min.

[0051] The carbonization in step 2 refers to heating the temperature to 270°C at a heating rate of 5.5°C / min under a nitrogen atmosphere, keeping the temperature for 32 minutes, and then heating the temperature to 655°C at a heating rate of 11°C / min, keeping the temperature for 1.1 hours.

[0052] The pulse activation in step 2 refers to first heating the temperature to 790°C at a heating rate of 21°C / min, keeping the temperature for 11 minutes, then cooling the temperature to 710°C, keeping the temperature for 33 minutes, and repeating the heating-keeping-cooling-keeping operation twice.

[0053] The water vapor pore expansion in step 2 refers to heating the sample at 2°C to 775°C, introducing water vapor at a flow rate of 63 mL / min, and treating for 15 minutes.

[0054] The post-treatment in step 2 is washing with 0.1 mol / L HCl at room temperature for 20 min, rinsing with deionized water until neutral, and drying in vacuo at 80°C.

[0055] The mass ratio of the composite material, carbon nanofiber, PTFE binder and anhydrous ethanol in step 3 is 2.8:0.7:2.5:4.

[0056] The ball milling in step 3 refers to ball milling at a speed of 150 rpm for 2.3 hours.

[0057] In step 4, the amount of slurry applied is 1.7 mg; the specification of the aluminum foil is 1 cm×1 cm; the drying refers to drying in an oven at 60°C for 10 minutes; the rolling temperature is 80°C; and the hot pressing refers to hot pressing at 120°C and 10PMa for 5 minutes.

[0058] Example 5 A process for preparing an activated carbon electrode material for a supercapacitor, the process comprising the following steps: Step 1: After sucrose, ammonium dihydrogen phosphate, and deionized water are uniformly stirred, zinc gluconate is added, mixed, and spray-dried at 80° C. to obtain a precursor powder with a loose structure; Step 2: Carbonizing the precursor powder with a loose structure and then performing pulse activation, steam pore expansion, cooling, and post-processing to obtain a composite material; Step 3: After the composite material, carbon nanofibers, and PTFE binder are evenly mixed, anhydrous ethanol is added, ball milled, and allowed to stand for degassing to obtain a slurry; Step 4: Coat the slurry on aluminum foil, dry it, roll it, and hot-press it to obtain the product.

[0059] The mass ratio of sucrose, ammonium dihydrogen phosphate, deionized water, and zinc gluconate in step 1 is 1.2:0.3:12:0.25.

[0060] The mixing in step 1 refers to stirring at 160 rpm in a 60° C. water bath for 40 min.

[0061] The carbonization in step 2 refers to heating the temperature to 280°C at a heating rate of 6°C / min under a nitrogen atmosphere, keeping the temperature for 35 minutes, then heating the temperature to 660°C at a heating rate of 12°C / min, and keeping the temperature for 1.2 hours.

[0062] The pulse activation in step 2 refers to first heating the temperature to 800°C at a heating rate of 22°C / min, keeping the temperature for 12 minutes, then cooling the temperature to 720°C, keeping the temperature for 35 minutes, and repeating the heating-keeping-cooling-keeping operation twice.

[0063] The water vapor pore expansion in step 2 refers to heating the sample at 2°C to 780°C, introducing water vapor at a flow rate of 65 mL / min, and treating for 15 minutes.

[0064] The post-treatment in step 2 is washing with 0.1 mol / L HCl at room temperature for 20 min, rinsing with deionized water until neutral, and drying in vacuo at 80°C.

[0065] The mass ratio of the composite material, carbon nanofiber, PTFE binder and anhydrous ethanol in step 3 is 2.9:0.8:2.6:4.2.

[0066] The ball milling in step 3 refers to ball milling at a speed of 160 rpm for 2.3 hours.

[0067] In step 4, the amount of slurry coated is 1.8 mg; the specification of the aluminum foil is 1 cm×1 cm; the drying refers to drying in an oven at 60°C for 10 minutes; the rolling temperature is 80°C; and the hot pressing molding refers to hot pressing at 120°C and 10PMa for 5 minutes.

[0068] Example 6 On the basis of Example 3, zinc gluconate was removed and replaced with ammonium citrate of equal weight, and other conditions remained the same as in Example 3.

[0069] Example 7 On the basis of Example 3, the mass ratio of sucrose, ammonium dihydrogen phosphate, deionized water, and zinc gluconate in step 1 was changed to 1.1:0.6:11:0.1.

[0070] Example 8 On the basis of Example 3, the mass ratio of sucrose, ammonium dihydrogen phosphate, deionized water and zinc gluconate in step 1 was 1.2:0.5:11:0.1.

[0071] Example 9 On the basis of Example 3, the mass ratio of sucrose, ammonium dihydrogen phosphate, deionized water and zinc gluconate in step 1 was 1.3:0.3:11:0.2.

[0072] Example 10 On the basis of Example 3, the mass ratio of sucrose, ammonium dihydrogen phosphate, deionized water and zinc gluconate in step 1 was 0.9:0.3:11.55:0.05.

[0073] Example 11 On the basis of Example 3, the mass ratio of the composite material, carbon nanofiber, PTFE binder, and anhydrous ethanol in step 3 was changed to 2.4:0.9:2.4:3.9.

[0074] Example 12 On the basis of Example 3, the mass ratio of the composite material, carbon nanofiber, PTFE binder, and anhydrous ethanol in step 3 was changed to 2.9:0.4:2.4:3.9.

[0075] Comparative Example 1 On the basis of Example 3, keeping other conditions the same, the preparation process was changed to the following steps: Step 1: Stir sucrose, ammonium dihydrogen phosphate, and deionized water until uniform, then add zinc gluconate and mix at 80° C. to obtain a mixture; Step 2: Carbonizing the mixture, pulse activating it, expanding the pores with water vapor, cooling it, and post-processing it to obtain a composite material; Step 3: After the composite material, carbon nanofibers, and PTFE binder are evenly mixed, anhydrous ethanol is added, ball milled, and allowed to stand for degassing to obtain a slurry; Step 4: Coat the slurry on aluminum foil, dry it, roll it, and hot-press it to obtain the product.

[0076] Comparative Example 2 On the basis of Example 3, keeping other conditions the same, the preparation process was changed to the following steps: Step 1: After sucrose, ammonium dihydrogen phosphate, and deionized water are uniformly stirred, zinc gluconate is added, mixed, and spray-dried at 80° C. to obtain a precursor powder with a loose structure; Step 2: Carbonizing the precursor powder with a loose structure and then performing pulse activation, steam pore expansion, cooling, and post-treatment to obtain a composite material; the carbonization refers to heating to 650°C at a heating rate of 5°C / min under a nitrogen atmosphere and holding the temperature for 1.5 hours; Step 3: After the composite material, carbon nanofibers, and PTFE binder are evenly mixed, anhydrous ethanol is added, ball milled, and allowed to stand for degassing to obtain a slurry; Step 4: Coat the slurry on aluminum foil, dry it, roll it, and hot-press it to obtain the product.

[0077] Comparative Example 3 On the basis of Example 3, keeping other conditions the same, the preparation process was changed to the following steps: Step 1: After sucrose, ammonium dihydrogen phosphate, and deionized water are uniformly stirred, zinc gluconate is added, mixed, and spray-dried at 80° C. to obtain a precursor powder with a loose structure; Step 2: Carbonizing the precursor powder with a loose structure and then performing pulse activation, steam pore expansion, cooling, and post-treatment to obtain a composite material; the carbonization refers to heating to 650°C at a heating rate of 10°C / min under a nitrogen atmosphere and keeping the temperature for 1.5 hours; Step 3: After the composite material, carbon nanofibers, and PTFE binder are evenly mixed, anhydrous ethanol is added, ball milled, and allowed to stand for degassing to obtain a slurry; Step 4: Coat the slurry on aluminum foil, dry it, roll it, and hot-press it to obtain the product.

[0078] Comparative Example 4 On the basis of Example 3, keeping other conditions the same, the preparation process was changed to the following steps: Step 1: After sucrose, ammonium dihydrogen phosphate, and deionized water are uniformly stirred, zinc gluconate is added, mixed, and spray-dried at 80° C. to obtain a precursor powder with a loose structure; Step 2: carbonizing and activating the precursor powder with a loose structure, expanding the pores with water vapor, cooling, and post-processing to obtain a composite material; the activation refers to heating to 780°C at a heating rate of 20°C / mind and keeping the temperature for 80 minutes; Step 3: After the composite material, carbon nanofibers, and PTFE binder are evenly mixed, anhydrous ethanol is added, ball milled, and allowed to stand for degassing to obtain a slurry; Step 4: Coat the slurry on aluminum foil, dry it, roll it, and hot-press it to obtain the product.

[0079] Comparative Example 5 On the basis of Example 3, keeping other conditions the same, the preparation process was changed to the following steps: Step 1: After sucrose, ammonium dihydrogen phosphate, and deionized water are uniformly stirred, zinc gluconate is added, mixed, and spray-dried at 80° C. to obtain a precursor powder with a loose structure; Step 2: Carbonizing the precursor powder with a loose structure and then performing pulse activation, steam pore expansion, cooling, and post-treatment to obtain a composite material; the pulse activation refers to heating to 780°C at a heating rate of 20°C / min, holding the temperature for 20 minutes, then cooling to 700°C and holding the temperature for 60 minutes; Step 3: After the composite material, carbon nanofibers, and PTFE binder are evenly mixed, anhydrous ethanol is added, ball milled, and allowed to stand for degassing to obtain a slurry; Step 4: Coat the slurry on aluminum foil, dry it, roll it, and hot-press it to obtain the product.

[0080] Comparative Example 6 On the basis of Example 3, keeping other conditions the same, the preparation process was changed to the following steps: Step 1: After sucrose, ammonium dihydrogen phosphate, and deionized water are uniformly stirred, zinc gluconate is added, mixed, and spray-dried at 80° C. to obtain a precursor powder with a loose structure; Step 2: Carbonizing the precursor powder with a loose structure and then performing pulse activation, cooling, and post-processing to obtain a composite material; Step 3: After the composite material, carbon nanofibers, and PTFE binder are evenly mixed, anhydrous ethanol is added, ball milled, and allowed to stand for degassing to obtain a slurry; Step 4: Coat the slurry on aluminum foil, dry it, roll it, and hot-press it to obtain the product.

[0081] Comparative Example 7 On the basis of Example 3, keeping other conditions the same, the preparation process was changed to the following steps: Step 1: After sucrose, ammonium dihydrogen phosphate, and deionized water are uniformly stirred, zinc gluconate is added, mixed, and spray-dried at 80° C. to obtain a precursor powder with a loose structure; Step 2: The precursor powder with a loose structure was heated to 650°C at a heating rate of 10°C / min1, kept warm for 1.5h, then heated to 780°C at a heating rate of 20°C / min, kept warm for 20min, then cooled to 700°C, kept warm for 60min, and then heated to 770°C at a rate of 1.5°C. After that, water vapor was introduced at a flow rate of 60mL / min, treated for 14min, cooled, and post-treated to obtain a composite material; Step 3: After the composite material, carbon nanofibers, and PTFE binder are evenly mixed, anhydrous ethanol is added, ball milled, and allowed to stand for degassing to obtain a slurry; Step 4: Coat the slurry on aluminum foil, dry it, roll it, and hot-press it to obtain the product.

[0082] The activated carbon electrode materials prepared in Examples 1-12 and Comparative Examples 1-7 were used as samples. The capacitance values ​​of the samples were tested in a 6M KOH solution using constant current charge and discharge at a current density of 1 A / g. The specific results are recorded in Table 1 below.

[0083] Table 1

[0084] As can be seen from Table 1, the activated carbon electrode material for supercapacitors prepared by the present invention can effectively improve the ion transmission efficiency, thereby improving the capacitance performance of the material.

[0085] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any person skilled in the art can make some changes or modifications to equivalent embodiments using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any indirect modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A process for preparing an activated carbon electrode material for a supercapacitor, characterized in that: The preparation process comprises the following steps: Step 1: After sucrose, ammonium dihydrogen phosphate, and deionized water are uniformly stirred, zinc gluconate is added, mixed, and spray-dried at 80° C. to obtain a precursor powder with a loose structure; Step 2: Carbonizing the precursor powder with a loose structure and then performing pulse activation, steam pore expansion, cooling, and post-processing to obtain a composite material; Step 3: After the composite material, carbon nanofibers, and PTFE binder are evenly mixed, anhydrous ethanol is added, ball milled, and allowed to stand for degassing to obtain a slurry; Step 4: Coat the slurry on aluminum foil, dry it, roll it, and hot-press it to form it.

2. The process for preparing an activated carbon electrode material for a supercapacitor according to claim 1, wherein: The mass ratio of sucrose, ammonium dihydrogen phosphate, deionized water and zinc gluconate in step 1 is 1-1.2:0.2-0.3:10-12:0.15-0.

25.

3. The process for preparing an activated carbon electrode material for a supercapacitor according to claim 1, wherein: The mixing in step 1 refers to stirring at 80-160 rpm in a 60° C. water bath for 30-40 min.

4. The process for preparing an activated carbon electrode material for a supercapacitor according to claim 1, wherein: The carbonization in step 2 refers to heating the material to 240-280°C at a heating rate of 4-6°C / min under a nitrogen atmosphere, keeping the temperature for 25-35 minutes, then heating the material to 640-660°C at a heating rate of 8-12°C / min, and keeping the temperature for 0.8-1.2 hours.

5. The process for preparing an activated carbon electrode material for a supercapacitor according to claim 1, wherein: The pulse activation in step 2 refers to first heating the temperature to 760-800°C at a heating rate of 18-22°C / min, keeping it warm for 8-12 minutes, then cooling it to 680-720°C, keeping it warm for 25-35 minutes, and repeating this heating-keeping-cooling-keeping operation twice.

6. The process for preparing an activated carbon electrode material for a supercapacitor according to claim 1, wherein: The water vapor pore expansion in step 2 refers to heating the mixture to 760-780° C. at a temperature of 1-2° C., then introducing water vapor at a flow rate of 55-65 mL / min for 13-15 minutes.

7. The process for preparing an activated carbon electrode material for a supercapacitor according to claim 1, wherein: The post-treatment in step 2 is washing with 0.1 mol / L HCl at room temperature for 20 min, rinsing with deionized water until neutral, and drying in vacuo at 80°C.

8. The process for preparing an activated carbon electrode material for a supercapacitor according to claim 1, wherein: In step 3, the mass ratio of the composite material, carbon nanofiber, PTFE binder and anhydrous ethanol is 2.5-2.9:0.4-0.8:2.2-2.6:3.6-4.

2.

9. The process for preparing an activated carbon electrode material for a supercapacitor according to claim 1, wherein: The ball milling in step 3 refers to ball milling at a speed of 120-160 rpm for 2.1-2.3 hours.

10. The process for preparing an activated carbon electrode material for a supercapacitor according to claim 1, wherein: In step 4, the coating amount of the slurry is 1.4-1.8 mg; the specification of the aluminum foil is 1 cm×1 cm; the drying refers to drying in an oven at 60°C for 10 minutes; the rolling temperature is 80°C; and the hot pressing molding refers to hot pressing at 120°C and 10PMa for 5 minutes.

Citation Information

Patent Citations

  • Universal method for preparing porous carbon material based on organic zinc salt

    CN109761216A

  • Lignin-based hierarchical porous carbon material with high mesoporous rate as well as preparation method and application of lignin-based hierarchical porous carbon material

    CN118702102A

  • Preparation method for sodium ion battery porous hard carbon material, and product and use thereof

    WO2024000885A1

Cited By

  • Water vapor activation device and method for porous carbon

    CN121317747A